Global Landscapes Forum 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Photos from a side event at the Global Landscapes Forum in Paris on 6 December 2015. Investing in agriculture is critical if we want to reduce poverty, address climate change, and tackle hunger. A climate change agreement in Paris is not likely to explicitly address agriculture – but countries are leading the way, by including action on agriculture in their Intended Nationally Determined Commitments (INDCs). Will these pledges be enough to deliver food security for billions of people and reduce agriculture’s climate change footprint? What further actions, commitments and finance are needed to safeguard the future of food and farming? The side event will consist of three interrelated sessions on ensuring food security under climate change through policies, integrated land use, new technologies and practices, and empowering women and youth. Event co-hosted by: The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS); the Technical Centre for Agricultural and Rural Cooperation (CTA), the Climate and Development Knowledge Network (CDKN), and the Food, Agriculture, Natural Resources Policy Analysis Network (FANRPAN), Pricewaterhouse Cooper (PwC). Photos: L. Mwamakamba (FANRPAN)